Custom design and biomechanical clinical trials of 3D‐printed polyether ether ketone femoral shaft prosthesis. Issue 9 (16th March 2022) - Wu, Chao; Zeng, Baifang; Deng, Jiayan; Shen, Danwei; Wang, Xiangyu; Tan, Lun; Liu, Xin; Qiu, Guigang
Abstract: During the surgical resection and reconstruction of a pathological femoral fracture, the removal of the femoral tumor leaves a large bone defect. Thus, it is necessary to reconstruct the defect and perform internal fixation. Polyether ether ketone (PEEK) has been widely used in spinal fusion and cranioplasty given its excellent biomechanical properties, biocompatibility, and stability. The typical design method of femoral prosthesis is based on the contralateral mirror image model (M‐model), and we propose a novel method for designing femoral prosthesis, which is based on the cross section and centerline of the mirrored femur (C‐model). In this study, the femoral shaft prostheses based on two models were manufactured using fused deposition modeling technology, and we use mechanical test and finite element analysis (FEA) to reveal the differences in mechanical properties of the two models. The mechanical results showed that the maximum loading force and yield strength were increased by 3% and 6% in the C‐model prosthesis compared with the M‐model prosthesis, respectively. In FEA, the results indicate that the C‐model prosthesis could reduce the stress concentration by 5.4%–10.9% compared to the M‐model prosthesis. Finally, the 3D‐printed PEEK femoral shaft prosthesis based on C‐model was implanted, no early complications occurred. Postoperative radiological examination indicated that the prosthesis and the femoral osteotomy end were closely matched and fixed well.